(untitled) (Latakia University Journal -Basic Sciences Series, 2014)
تناول هذا البحث دراسة تأثير أهم الشروط التحليلية والتقنية في المنحنيات الفولط أمبيرومترية للرصاص والكادميوم , وذلك من أجل اختيار الشروط المثلى للتحديد المتزامن لهذين العنصرين بالطريقة الفولط أمبيرومترية التراكمية الأنودية النبضية التفاضلية DPASV , باستخدام مسرى الغرافيت المغطى بفيلم من الزئبق GMFE بصفة مسرى عامل . أظهرت النتائج أن الشروط التحليلية المثلى كانت عند استخدام إلكتروليت خلات الصوديوم – حمض الخل بتركيز 0.05M , حيث pH= 4.6, وتركيز قدره 25mg/l من Hg2+ , ونسبة CCd:CPb حتى 1:10 وبالعكس, أما بالنسبة للشروط التقنية المثلى فكانت بتطبيق مجال مسح كموني من -1200mV إلى -100mV عند كمون تراكم Eacc= -1200mV وزمن تراكم tacc= 120sec, وسرعة مسح 120mV/sec, وسعة نبضة 50mV . أعطت الشروط السابقة عند تطبيقها منحنيات فولط أمبيرومترية مثاليةIp(Cd)= 6.134µA , Ip(Pb)= 4.966µA,Ep(Cd)= -647mV , Ep(Pb)= -473mV. طبقت الشروط السابقة على عيّنة قياسية وتم الوصول إلى حدّ كشف قدره 0.100µg/l (Cd) , 1.000µg/l (Pb) , ومعامل الاسترجاع 100.5% =(Cd)R% و= 97.2%(Pb)R% , والانحراف المعياري 0.020mg/l =(Cd)SD و0.021mg/l =(Pb)SD, وهذا يدل على مدى صحة الطريقة ودقتها. درست صلاحية الطريقة بشروطها الجديدة على عدد من العينات البيئية فأبدت نجاحاً وكفاءة عالية. This research studying the effect of the most important analytical and technical conditions on the voltammetric curves of lead and cadmium in order to choose the optimal conditions for the simultaneous determination of these two elements by Differential pulse anodic stripping voltammetry (DPASV) using Graphite mercury film electrode(GMFE) as a working electrode. The results showed that the optimum analytical conditions were when using Sodium acetate - acetic acid (0.05M) electrolyte, where pH= 4.6, and a concentration (25mg/l) of Hg2+, CCd:CPb ratio up to 1:10 and conversely, and the optimum technical conditions were when applying scanning field from -1200 to -100mV, accumulation potential Eacc= -1200mV, accumulation time tacc= 120sec, speed rate υ= 120mV/sec, and amplitude pulse ΔE= 50mV. The previous conditions gave ideal voltammetric curves, Ip(Cd)= 6.134µA, Ip(Pb)= 4.966µA, Ep(Cd) = -647 mV, Ep(Pb)= -473 mV. The previous conditions were applied on a standard sample and the limit of detection was (Cd) 0.100µg/l, (Pb) 1.000µg/l, retrieval coefficient R%(Cd)= 100.5%, R%(Pb)= 97.2%, standard deviation SD(Cd)= 0.020mg/l, SD(Pb)= 0.021mg/l; Therefore, that shows the accuracy and precision of the method. The validity of the method under its new conditions was examined on a number of environmental samples and showed success and high efficiency.